The quest for a molecular capsule assembled via halogen bonds - Aakeröy, Christer B.; Rajbanshi, Arbin; Metrangolo, Pierangelo; Resnati, Giuseppe; Parisi, Melchiorre F.; Desper, John; Pilati, Tullio (My University, 2012)
A halogen-bonded capsule is obtained via directed assembly of a rigid tetra(3-pyridyl) cavitand and a flexible tetra(4-iodotetrafluorophenyl) calix[4]arene. The pyridyl nitrogen atoms from one cavitand molecule interact with the iodine atoms of a single calixarene molecule through short and directional I…N halogen bonds. The flexibility of the ethylenedioxy moieties on the calixarene platform results in positional flexibility of the iodotetrafluorobenzene sites which, coupled with a supramolecular chelating effect, allow for an effective partner-induced geometric fitting between four nitrogen atoms on the cavitand and four iodine atoms on the calixarene.
Keywords: Halogen bonds; Molecular capsule; Cavitand; Calixarene